(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
This study aims to determine the Quality of Elderly Public Health Services at the Duono Health Center, Ibu Tabaru District, West Halmahera Regency. This type of research uses qualitative descriptive. All data that have been presented are in accordance with primary and secondary data. Based on the results of the study according to the indicators, namely accuracy in service time, courtesy and friendliness when providing services, ease of getting service, and consumer comfort. But what happened at the Duono Health Center until now the quality of service has not been going well, this is indicated by the lack of facilities and infrastructure provided so that it is not in accordance with the number of visits, besides that there are facilities and infrastructure that are poorly maintained so that they do not provide comfort for the community/ elderly patients at the Duono Health Center, there are still service officers who provide services that are not according to the stated schedule. The number of medical personnel at the Duono Health Center, in this case Doctors, Midwives, and Nurses, is still lacking and not balanced. There are still employees or medical personnel who are not on time in providing health services, lack of friendliness in providing services and cannot provide comfort in providing services. Elderly public health services must be further improved so that the Quality of Elderly Public Health Services at the Duono Health Center is more effective. Keywords : Quality, Health Services, Elderly Society